Hepatocellular Carcinoma to the Right Ventricle - George R. Marzouka; Apurva Badheka; Alexis P. Rodriguez; Sandra V. Chaparro (Case Reports in Cardiology)
Hepatocellular carcinoma (HCC) is the sixth most prevalent cancer in the world, but metastatic disease to the heart is rare. We present a case of a 63-year-old man with history of hepatitis C and cirrhosis, which had progressed to HCC. The patient had undergone two prior liver transplantations. He presented to the hospital complaining of worsening lower extremity edema. His exam was also pertinent for jugular venous distension, a 3/6 crescendo-decrescendo murmur, and hepatosplenomegaly. A transthoracic echocardiogram showed a large irregular lobulated mass in the apex of the right ventricle with a mobile pedunculated component. An MRI of the heart revealed a 4.4 × 3.4 × 4.0 cm mass within the right ventricular apex, which was subsequently biopsied and found to be moderately differentiated HCC with myocardial fragments. The patient opted out of any further therapy, or intervention, and was enrolled in hospice care.